Pediatric drug information available at the time of new drug approvals: A cross‐sectional analysis. Issue 2 (17th November 2017) - Hudgins, Joel D.; Bacho, Matthew A.; Olsen, Karen L.; Bourgeois, Florence T.
Abstract: Purpose: Greater than 50% of drugs lack pediatric labeling information, resulting in widespread "off‐label" use in children. To increase pediatric prescribing information, the Pediatric Research Equity Act (PREA) was passed in 2003, requiring new drug applications to include pediatric assessments. We evaluated the study of new drugs in children since PREA was implemented. Methods: We performed a cross‐sectional analysis of new drug applications submitted to the FDA from December 2003 to July 2012, using publicly available documents at Drugs@FDA. We calculated the proportion of new drugs that included a pediatric assessment at the time of approval and at a final review performed in July 2016. Results: We identified 92 new drugs requiring pediatric assessments. Only 20 (21.7%) had been fully studied in children at the time of approval, while 9 (9.8%) had been partially assessed, and 63 (68.5%) did not have pediatric data. Among drugs approved without pediatric assessments, 4.2% met FDA deferral deadlines and 34.9% eventually submitted pediatric data. At the time of our final review, allowing for a mean of 8.6 years since drug approval, 57.6% of new drugs had not been fully assessed in children. The mean time between approval in adults and availability of pediatric data for drugs approved without pediatric assessments was 6.5 years. Conclusions: These results represent a comprehensive evaluation of the study of new drugs in children and demonstrate that many drugs continue to be approved without pediatric data. Our findings serve to inform approaches to strengthen adherence to PREA requirements.